FAKTOR-FAKTOR KEPUTUSAN PEMBELIAN KERIPIK PISANG ASKHA JAYA - Annisa Karinina; Dadang Karya Bakti; Ghia Subagja (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
The purpose of this study was to determine the factors of the decision to buy Askha Jaya banana chips. The method used in this study is a descriptive method with a qualitative approach. The result of this study is that banana chips in Lampung are so identical to Askha Jaya and become the most preferred product for consumers because of the distinctive taste that distinguishes it from other brands so that there are 5 factors formed after the interview. The first factor is the product attribute factor related to the taste of Askha Jaya banana chips which has characteristics in the seasoning, affordable prices, a comfortable place with a storefront arrangement that is pleasing to the eye and a large parking lot, and packaging that is various and safe to take to distant places. Cultural factors consisting of consumers who come to male-dominant stores, as well as the widely known brand name Askha Jaya so that it becomes a reason for consumers to return to shopping for banana chips there every time they come to Lampung, social factors are a social interaction of an Askha Jaya consumer who is able to influence others to choose Askha Jaya banana chips, Personal factors include consumer lifestyles that follow trends, social status which is a demand to be more prestigious, jobs and economic situations that support consumers to be able to maintain their loyalty to Askha Jaya banana chips, and personality and self-concept that greatly influence, psychological factors that are a learning process for consumers, therefore the arrival of consumers to Askha Jaya stores certainly has its own purpose that can provide benefits for those consumers or those around them.